Turning Society into Graphs: Early 20th Century Statistical Undertakings in Shanxi Province - Bréard, Andrea; Christ, Stefan; Tang, Lina (Journal of the European Association for Chinese Studies, 2025)
While no census was ever successfully completed for all of China under the Republic, the poor province of Shanxi, ruled by warlord Yan Xishan, published new population statistics every year from 1919. The province's Statistical Office not only consistently collected various statistical data, it was also a pioneer with respect to graphical statistics. Why did Shanxi produce so many statistics? Who produced them, and for what purpose? How did they figure into the modernisation and state-building attempts by Yan Xishan? What can we learn about his concerns regarding the population from the collected statistical materials? How is statistical knowledge and information made visible in statistical diagrams, what meaning is created, and which arguments are made through visual semantics? To tackle these questions, we examine relevant actors and institutions, closely read Yan Xishan’s preface to the earliest population statistics published in Shanxi, and finally look at the statistics and graphics published there between 1919 and 193
Keywords: Statistics; Yan Xishan; Shanxi; Republican China; Statistical Graphs; Population